Peningkatan Penguasaan Kosa Kata Nama Anggota Tubuh Manusia Menggunakan Media Poster pada Anak Tunagrahita Ringan Kelas III di SLB Negeri Kota Radja Kupang - Bira, Ester Yuni Milka; Selan, Ot Bil Wilson; Wangge, Vinsensius; Liunokas, Oded; Ajito, Timoteus; Wora, Dionosius (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This classroom action research aims to improve the mastery of human body part vocabulary among four mild intellectually disabled students in Class III at SLB Negeri Kota Radja Kupang, who previously experienced difficulties in recognizing, naming, pointing out, and matching this basic vocabulary. The research subjects consisted of 4 students (2 males and 2 females). The method used is descriptive quantitative Classroom Action Research (CAR) with the Kemmis and Mc Taggart model, which includes planning, acting, observing, and reflecting. The intervention medium used was a poster medium, chosen for its ability to present information visually, simply, clearly, and to capture the attention of mild intellectually disabled children. The study was conducted in two cycles. The results of the data analysis show a significant increase. The students' average scores in the pre-action (pre-test) were in the poor and sufficient categories, then increased in Cycle I (post-test I), and reached a maximum improvement in Cycle II (post-test II) with a very good category. The conclusion of this study is that the use of the poster medium is effective and can enhance the mastery of human body part vocabulary in mild intellectually disabled children at SLB Negeri Kota Radja Kupang